Expression of insulin/insulin‐like signalling and TOR pathway genes in honey bee caste determination. Issue 1 (14th November 2013) - Wheeler, D. E.; Buck, N. A.; Evans, J. D.
Abstract The development of queen and worker castes in honey bees is induced by differential nutrition, with future queens and workers receiving diets that are qualitatively and quantitatively different. We monitored the gene expression of 14 genes for components of the insulin/insulin‐like signalling and TOR pathways in honey bee larvae from 40–88 h after hatching. We compared normally fed queen and normally fed worker larvae and found that three genes showed expression differences in 40‐h‐old larvae. Genes that show such early differences in expression may be part of the mechanism that transduces nutrition level into a hormone signal. We then compared changes in expression after shifts in diet with those in normally developing queens and workers. Following a shift to the worker diet, the expression of 9/14 genes was upregulated in comparison with queens. Following a shift to the queen diet, expression of only one gene changed. The honey bee responses may function together as a homeostatic mechanism buffering larvae from caste‐disrupting variation in nutrition. The different responses would be part of the canalization of both the queen and worker developmental pathways, and as such, a signature of advanced sociality.